Tuning the Excited State of Water‐Soluble IrIII‐Based DNA Intercalators that are Isostructural with [RuII(NN)2(dppz)] Light‐Switch Complexes1. Issue 10 (22nd January 2015) - Stimpson, Sasha; Jenkinson, Dan R.; Sadler, Andrew; Latham, Mark; Wragg, Dr Ashley; Meijer, Anthony J. H. M.; Thomas, Jim A.
Abstract The synthesis of two new IrIII complexes which are effectively isostructural with well‐established [Ru(NN)2(dppz)]2+ systems is reported (dppz=dipyridophenazine; NN=2, 2′‐bipyridyl, or 1, 10‐phenanthroline). One of these IrIII complexes is tricationic and has a conventional N6 coordination sphere. The second dicationic complex has a N5C coordination sphere, incorporating a cyclometalated analogue of the dppz ligand. Both complexes show good water solubility. Experimental and computational studies show that the photoexcited states of the two complexes are very different from each other and also differ from their RuII analogues. Both of the complexes bind to duplex DNA with affinities that are two orders of magnitude higher than previously reported Ir(dppz)‐based systems and are comparable with RuII(dppz) analogues.